Análise da decomposição estrutural: uma abordagem do Plano de Desenvolvimento Regional Sustentável da Região de Integração do Xingu, Pará - FILGUEIRAS, Gisalda Carvalho (2022)
The Xingu Sustainable Regional Development Plan – PDRSXingu aimed to implement policies that promote sustainable development and improve the quality of life of the population. The municipalities of the Xingu Integration Region are in the area covered by SUDAM and it is understood that it is pertinent to monitor the implementation of the Hydroeletric Plant - Belo Monte HPP. The works began in 2011 and was inaugurated in 2016 and fully implemented in 2019. In March/2016, the main structures and assets used for the construction of the project were demobilized. Considering this Plan, this article aimed to analyze the same, both in terms prior to its implementation (2008), as well as after its completion (2015). The application of the input matrixes product (IMP) of the aforementioned years was used, and by the variable use, the structural decomposition analysis (SDA) was performed. The result showed that it is not enough to implement and move a project in the medium term, but to introduce alternatives for local development after the completion of a large work the Belo Monte HPP, because, necessarily when a work ends, in this large case, funding is emptied and with it jobs, income, with great loss to the local and regional market.